MOISTURE-RELATED BUILDING DEFECTS IN HERITAGE BUILDING: A REFURBISHMENT-BASED ASSESSMENT - Yacub, Mirzal; Salleh, Naziah Muhammad (Border: Jurnal Arsitektur, 2025)
Moisture-related building defects in Penang’s heritage buildings persist despite refurbishment efforts, posing threats to structural integrity, aesthetics, and occupant comfort. This problem is exacerbated by tropical coastal conditions, stringent conservation guidelines mandating original materials (e.g., lime), and the inherent vulnerability of aged structures. This study employed a mixed-methods approach, combining field surveys (thermal imaging, humidity tests) and user questionnaires across three refurbished heritage buildings (hotel): 23 Love Lane (strict WHS compliance), Jawi Peranakan Mansion (moderate), and USM Guesthouse (weak compliance). Quantitative data were analyzed via SPSS (descriptive statistics, chi-square tests). Key results revealed: (1) Moisture-driven defects (dampness, fungi, peeling paint) recurred in all buildings, with severity highest under strict compliance (27 defects at 23 Love Lane); (2) Weak-compliance USM Guesthouse used cement, reducing moisture ingress but violating authenticity; (3) User surveys identified peeling paint discomfort as significant concerns (P<0.05). The implications underscore a critical dilemma: strict material preservation perpetuates moisture susceptibility, while modern substitutions compromise heritage values. Effective refurbishment guidelines must integrate moisture-mitigation strategies compatible with historical materials and tropical environments.